Plasma single-stranded DNA autoantibodies in the diagnosis of Hirschsprung’s disease - Wang, Bingtong; Yao, Yongxuan; Fang, Wenlin; Liu, Yanqing; Zhong, Wei; He, Ye; Lai, Yulu; He, Qiuming; Zhu, Yun; Lan, Chaoting (Frontiers in Medicine, 2022)
Background: Hirschsprung's disease (HSCR) is a neonatal enteric nervous system (ENS) disease characterized by congenital enteric ganglion cell loss. The only treatment is aganglionic bowel segment resection and innervated bowel segment reconstruction. Delayed diagnosis and treatment cause postoperative complications such as intractable constipation and enterocolitis. Existing preoperative HSCR diagnostic methods have shortcomings such as false positives, radiation and invasiveness. Methods: We used the robust linear model (RLM) for normalization and the M statistic for screening plasma human autoimmune antigen microarrays and quantitatively assessed single-stranded (ssDNA) antibody levels with enzyme-linked immunosorbent assay (ELISA). Results: The autoimmune antigen microarray revealed that autoantibodies were higher in HSCR plasma than in disease control (DC) and healthy control (HC) plasma. ssDNA antibodies in HSCR plasma were significantly higher than those in DC and HC plasma. Quantitative ssDNA antibody level detection in plasma by ELISA showed that HSCR (n=32) was 1.3-fold and 1.7-fold higher than DC (n=14) and HC (n=25), respectively. ssDNA antibodies distinguished HSCR from non-HSCR (HC and DC), achieving an area under the curve (AUC) of 0.917 (95% CI, 0.8550 to 0.9784), with a sensitivity of 96.99% and a specificity of 74.63%. Conclusion: ssDNA antibodies in plasma can serve as a diagnostic biomarker for HSCR in the clinic. Keywords: ENS; HSCR; ssDNA antibodies; early diagnosis of HSCR; ELISA